Topical Gel Formulated With Ziziphus Spina-Christi Leaf Extract Decreases Lymphocyte Infiltration in Gingival Incision Wounds - I Gusti Ayu Dewi Haryani; Hervina; Made Talitha Suryaningsih Pinatih; Lee Youngwoo (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Gingival wounds are injuries in the oral cavity that may be caused by various factors such as trauma, infection, and periodontal disease. The wound healing process involves the activation of multiple immune cells, including lymphocytes. Lymphocytes are one of the three main types of phagocytic cells in the immune system and play a vital role in both innate and adaptive immunity, being widely distributed throughout body tissues. One potential alternative material that may accelerate wound healing is the leaf of Ziziphus spina-christi L. (Arab Bidara), which is known to contain several secondary metabolites, including alkaloids, flavonoids, saponins, steroids, and lipids, with wound-healing properties. This study is to investigate the effect of Arab Bidara leaf extract gel on lymphocyte count in gingival incision wounds of male Wistar rats (Rattus norvegicus). Materials and methods: This study was a randomized posttest-only control group experimental design. A total of 30 male Wistar rats were divided into three groups: a control group receiving Gengigel®, a placebo group, and a treatment group administered Arab Bidara (Ziziphus spina-christi L.) leaf extract gel. The gel was applied topically in the oral cavity for six consecutive days. Observations were conducted on days 3 and 5. Results and Discussion: The results showed an increase in lymphocyte count on day 3 and a significant decrease in lymphocyte count on day 5 in the treatment group. Conclusion: It can be concluded that the administration of Arab Bidara leaf extract gel has an effect on reducing lymphocyte count and is effective in accelerating gingival wound healing.